Investitionen und Emissionen von Convertible Bonds (Wandelanleihen) - Thomas Heidorn; Mirko Gerhold (Hochschule für Bankwirtschaft (HfB), 2004)
Convertible bond issues increase considerably since 1990. The paper shows that these issues are more than just the combination of a bond and an option. The pricing depends on the share price, the shares volatility, the interest rate, and the interest volatility , the credit spread, and the correlation among them. Convertibles are especially helpful for non rated or low rated companies. The information asymmetry between management and investor can be considerably reduced compared to bond or share issues.
urn:nbn:de:101:1-2008072222
Keywords: G12; 330; hybrids; convertible arbitrage; hedge fonds; issue of convertibles; investing in convertibles